Simulation Study Of Heat Exchanger Design - Ahmad, Wan Mohd Alimie Wan (Universiti Sains Malaysia, 2017)
Heat exchangers are used to transfer heat from fluid at high temperature to fluid at lower temperature. Heat exchangers are used in industrial purposes in chemical industries, nuclear power plants, refineries, food processing, etc. Sizing of heat exchangers plays very significant role for cost optimization. Also, efficiency and effectiveness of heat exchangers is an important parameter while selection of industrial heat exchangers. Methods for improvement on heat transfer have been worked upon for many years in order to obtain high efficiency with optimum cost. In this project, we are analyzing shell and tube heat exchanger with baffle plates by changing tube material. The process in solving simulation consists of modeling and meshing the basic geometry of shell and tube heat exchanger using FLUENT package ANSYS 14.0. Dimensions for the model are taken by existing heat exchanger used by PETRONAS Carigali SDN BHD. In this project, modeling of shell and tube heat exchanger with baffles tubes and supports created by using GAMBIT software. Then, the boundary condition will be set and simulate in FLUENT based on the industrial data. The scope of this paper is to study the heat transfer rate of heat exchanger using ANSYS FLUENT 14.0 software tool. The flow and temperature fields inside the shell and tube are resolved using a commercial FLUENT package. Our heat exchanger consists of two fluids (crude oil and Danol-XHT) of different starting temperatures flow through the heat exchanger. Heat transfer rate of the heat exchanger were calculated by mathematical modeling equations. Tubes were varied with different materials likes copper, aluminum, carbon steel and graphene. Finally analysis has been done by varying the tube materials and hence it is observed that copper material gives the better heat transfer rates than aluminum, carbon steel and graphene.